1974
DOI: 10.1085/jgp.64.4.393
|View full text |Cite
|
Sign up to set email alerts
|

Functional Separation of the Na-K Exchange Pump from the Volume Controlling Mechanism in Enlarged Duck Red Cells

Abstract: Previous publications have described a "volume controlling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1976
1976
1992
1992

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Cell swelling has been reported to activate (K + Cl) cotransport in avian erythrocytes (Kregenow, 1974;Kregenow and Caryk, 1979;Haas and McManus, 1985). The swelling-activated, Cl-dependent K transport in sheep erythrocytes Dunham and Ellory, 1981) is also postulated to be (K + Cl) cotransport (Lauf, 1985).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Cell swelling has been reported to activate (K + Cl) cotransport in avian erythrocytes (Kregenow, 1974;Kregenow and Caryk, 1979;Haas and McManus, 1985). The swelling-activated, Cl-dependent K transport in sheep erythrocytes Dunham and Ellory, 1981) is also postulated to be (K + Cl) cotransport (Lauf, 1985).…”
Section: Discussionmentioning
confidence: 98%
“…In particular, swelling has been reported to activate Cldependent K transport in avian (Kregenow, 1974 ;Kregenow and Caryk, 1979 ;Haas and McManus, 1985), sheep Dunham and Ellory, 1981 ;Lauf, 1984), dog (Parker, 1983), and toadfish erythrocytes (Lauf, 1985), K/H exchange in Amphiuma erythrocytes (Gala, 1983), K conductance in human lymphocytes (Sarkadi et al ., 1985) and Ehrlich ascites tumor cells (Hoffmann et al ., 1984), and K loss through an unidentified mechanism in flounder erythrocytes (Gala, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Thus many invertebrate tissues lose cellular amino acids when exposed to hyposmotic media (Schoffeniels, 1967). Recently it has been shown that duck erythrocytes exposed tohyposmotic media lose potassium and thereby chloride (Kregenow, 1971(Kregenow, , 1973(Kregenow, , 1974 and that these losses are not affected by ouabain (Kregenow, 1971). Dellasega & Grantham (1973) have suggested that the regulation of cellular volume in renal tubular cells exposed to hyposmotic medium may involve a similar loss of potassium and chloride.…”
Section: Introductionmentioning
confidence: 99%
“…More recently in a preliminary report they have suggested that losses of both potassium and sodium may be involved (Grantham, Lowe & Dellasega, 1974). Thus it has been suggested that cellular potassium plays a central role in protecting cells from undue swellinginhyposmotic medium, perhaps as a result ofchanges inmembrane permeability to potassium under these conditions (Kregenow, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…The study of volume regulation by duck red blood cells was pioneered by Kregenow [164,167], who showed that following osmotic swelling the duck red cell regulates its volume back to control levels (RVD) in about 90 min. This RVD results from activation of a transport system which mediates an efflux of K + and CI-from the cells driven by the K + concentration gradient [164].…”
Section: Duck Red Cellsmentioning
confidence: 99%